'But There Are No Lions in the Scottish Highlands': Reading the trunk in Matka. Issue 1 (1st April 2014) - Wei, John
This article reads the trunk in Matka as Lacan's objet petit a – a reminder of our desiring subjectivity and considers to what degree it might be seen as a MacGuffin. It also argues that the protagonist is an emblem of the human subject in an abstract representation of our life's journey.